Balancing tradition and tomorrow: smart growth strategies for the sustainability of rural communities - Pfeifer, Caden L. (Kansas State University, 2024)
In the post-World War II era, the globalization of U.S. cities has triggered population decline in many rural communities, prompting a quest for solutions to sustain their prosperity. However, concerns have arisen regarding the impact of standardized development regulations on these communities, affecting their ambiance and distinctive, place-specific character. This research delves into the intricate balance required to foster growth while preserving the unique character of rural communities. Central to this investigation is exploring the Smart Growth concept as a potential solution to enhance local development regulations and safeguard the essence of small towns by taking Dodge City and Garden City, as case studies. The study aims to determine how integrating Smart Growth principles can contribute to addressing challenges related to rural community character. Doing so establishes a foundational understanding for future researchers to delve into applying Smart Growth principles in the rural context, with considerations for broader implications in sustainable planning.
Keywords: Smart growth; Rural character; Planning; Sustainibility